2017
DOI: 10.1186/s40981-017-0128-z
|View full text |Cite
|
Sign up to set email alerts
|

Adhesions in the epidural space caused by frequent epidural blocks

Abstract: We report a case of adhesions in the epidural space caused by more than 200 times epidural blocks that were observed with epiduroscopy. A 41-year-old man had repeatedly undergone lumbar epidural blocks to treat pain in his leg, resulting in decreased efficacy of the epidural block. We described endoscopic findings that these adhesions were mostly consisted of adhesions formed from the soft connective tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Parturients with previous epidural experience had a higher failure rate than those who received EA for the rst time. A previous study has reported signi cant in ammatory changes and adhesions using the epidural scope in patients with a history of EA [20,21]. Puncture of the ava ligament and epidural catheterization lead to congestion and adhesions in the epidural space, resulting in disturbance in the local anesthetic spread in the epidural space [22].…”
Section: Discussionmentioning
confidence: 97%
“…Parturients with previous epidural experience had a higher failure rate than those who received EA for the rst time. A previous study has reported signi cant in ammatory changes and adhesions using the epidural scope in patients with a history of EA [20,21]. Puncture of the ava ligament and epidural catheterization lead to congestion and adhesions in the epidural space, resulting in disturbance in the local anesthetic spread in the epidural space [22].…”
Section: Discussionmentioning
confidence: 97%
“…The difference operation time between the 2 procedures were attributed to the distinct nature of both surgical procedures, such as patient-specific factors, equipment used, or the skill and experience of the surgeon. [41][42][43] With miniaturized endoscopic tools, the operation can provide a clearer visualization and potentially decrease postoperative complications due to reduced tissue trauma. However, there's a trade-off that smaller instruments may require more precise handling, meticulous maneuvers, and sometimes multiple instrument changes to achieve the desired outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the operation time is longer compared to the MLD procedure. The difference operation time between the 2 procedures were attributed to the distinct nature of both surgical procedures, such as patient-specific factors, equipment used, or the skill and experience of the surgeon [ 41 - 43 ]. With miniaturized endoscopic tools, the operation can provide a clearer visualization and potentially decrease postoperative complications due to reduced tissue trauma.…”
Section: Discussionmentioning
confidence: 99%
“…14 Shi-mada et al, also suggested that local inflammation caused adhesion in the epidural space. 15 Because the lumbar nerve as well as the dural sac in the spinal canal requires adequate mobility and spaces, the environment around the EFT and dural sac needs to be in a low-inflammatory condition to prevent adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fujita et al reported that EFT in lipomatosis patients had significantly increased expression of inflammatory cytokines which are related to chronic inflammation in the spinal canal 14 . Shi- mada et al , also suggested that local inflammation caused adhesion in the epidural space 15 . Because the lumbar nerve as well as the dural sac in the spinal canal requires adequate mobility and spaces, the environment around the EFT and dural sac needs to be in a low-inflammatory condition to prevent adhesion.…”
Section: Discussionmentioning
confidence: 99%